2018
DOI: 10.1039/c8fo00735g
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a low and a high dietary LA/ALA ratio on long-chain PUFA concentrations in red blood cells

Abstract: aThere is a debate about the optimal dietary ratio of the parent n6 fatty acid linoleic acid (LA) and n3 fatty acid alpha-linolenic acid (ALA) to promote an efficient conversion of ALA to EPA and DHA, which have implications for human health. The aim of the present study was to compare the effects of a low-LA/ high-ALA ( lo LA/ hi ALA) diet with a high-LA/low-ALA ( hi LA/ lo ALA) diet on fatty acid concentrations in red blood cells (RBCs). Fifteen omnivore healthy men (mean age 26.1 ± 4.5 years) with a low ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 57 publications
2
18
2
Order By: Relevance
“…Regarding the conversion of ALA into n-3 PUFA studies have shown that a higher intake of ALA increases the levels of EPA in erythrocytes in humans (Barceló-Coblijn et al, 2008; Table 4. Goyens et al, 2006;Greupner et al, 2018). In our study, vegans consumed 190% more ALA than omnivores and no significant differences were observed in the intake of LA between groups.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Regarding the conversion of ALA into n-3 PUFA studies have shown that a higher intake of ALA increases the levels of EPA in erythrocytes in humans (Barceló-Coblijn et al, 2008; Table 4. Goyens et al, 2006;Greupner et al, 2018). In our study, vegans consumed 190% more ALA than omnivores and no significant differences were observed in the intake of LA between groups.…”
Section: Discussioncontrasting
confidence: 52%
“…This differential pattern could be related to (1) the low rate of conversion of ALA to DHA in humans (less than 1%) (Brenna et al, 2009), or (2) the preferential incorporation of preformed EPA and DHA into these tissues. Regarding the conversion of ALA into n‐3 PUFA studies have shown that a higher intake of ALA increases the levels of EPA in erythrocytes in humans (Barceló‐Coblijn et al, 2008; Goyens et al, 2006; Greupner et al, 2018). In our study, vegans consumed 190% more ALA than omnivores and no significant differences were observed in the intake of LA between groups.…”
Section: Discussionmentioning
confidence: 99%
“…Our results revealed a PUFA/SFA ratio (0.07-0.09) considerably lower than 0.45 and a ratio of n-6/n-3 PUFA (1.49-1.92) within the recommended levels. There is a debate about the optimal dietary ratio of the parent n-6 FA linoleic acid to the n-3 FA ALA to promote efficient conversion of ALA to eicosapentaenoic and docosahexaenoic acid, both of which have positive implications for human health [46]. In the present study, linoleic acid decreased towards the end of lactation, while ALA remained constant; thus, the lowest ratio of these FAs was observed when milk production decreased.…”
Section: Discussionmentioning
confidence: 45%
“…The LA:ALA ratios for our study population-−8.98 for non-vegetarians and 9.90 for vegetarians—are lower compared to the US adolescent population (weighted mean = 11.1). A lower LA:ALA ratio is considered favorable since the dietary ratio of LA (the parent n-6) to ALA (the parent n-3) had been shown to affect ALA conversion to the physiologically important very long-chain n-3 fatty acids, EPA and DHA, in the red blood cells (36, 37). A lower LA intake and a LA:ALA ratio <10 may improve this conversion and also reduce arachidonic acid (37), the precursor of pro-inflammatory eicosanoids.…”
Section: Discussionmentioning
confidence: 99%